Using genetic algorithm (ga) to create a pid speed controller for three-phase induction motor - Trần Tấn Khang; Nguyễn Minh Tâm (Journal of Technical Education Science, 2012)
The aim of this paper is to create a PID speed controller for three-phase induction motor by using genetic algorithm (GA) and the field oriented control (FOC) method of induction motor. In addition, a speed-estimation process with the model referencing adaptive system (MRAS) was presented in detail. The estimated-modelling also used the GA to identify PI-index for tuning speed error. The Genetic PID-speed controller software was implemented using the Matlab-simulink version 2009a. This paper’s results are compared with two kinds of tuning methods of parameter for PID controller. One is the controller design by the Fuzzy logic and the other is the Particle swarm optimization (PSO). Results showed that the proposed PID parameters adjustment by the GA is better than the Fuzzy method. Results of the GA and PSO are at the same level